2018
DOI: 10.1177/0974686218806714
|View full text |Cite
|
Sign up to set email alerts
|

CEOs’ Characteristics and Firm Performance: A Study of Indian Firms

Abstract: The centre of interest of this research article is the association between chief executive officer (CEO) characteristics and firm performance. Employing a sample of Nifty 500 firms, the support found recommends that demographic and job-related characteristics may be related with the firm's financial performance. We consider CEO gender, duality, nationality, remuneration and education level as CEO characteristics and we employ return on assets (ROA) as a representative for firm performance. This study widens th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 63 publications
5
38
0
4
Order By: Relevance
“…To address scams, corruptions, and ineffective corporate governance, the Companies Act 2013 in India has streamlined the corporate structures and processes (Kaur & Singh, 2018). The reason for streamlining corporate governance structure is to bring transparency, efficiency, reduce information asymmetry, and to minimize inequity in prevailing compensation of CEOs (Baker, Bivens, & Schieder, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To address scams, corruptions, and ineffective corporate governance, the Companies Act 2013 in India has streamlined the corporate structures and processes (Kaur & Singh, 2018). The reason for streamlining corporate governance structure is to bring transparency, efficiency, reduce information asymmetry, and to minimize inequity in prevailing compensation of CEOs (Baker, Bivens, & Schieder, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study also focused on the cross-holding of directorships in family business groups and found the positive association of cross-holdings of executive directors with the financial performance of the firm. Kaur and Singh (2018) found a positive association between CEO remuneration and firm performance, and study also found the CEO nationality has its impact on this relationship. Kohli and Gill (2019) examine the relationship between corporate strategy and CEO compensation in the case of family firms in India by using a sample of 106 listed pharmaceutical companies in India.…”
Section: Ceo Compensation and Corporate Governance In Indian Firmsmentioning
confidence: 65%
“…В исследованиях [Gerhart, Milkovich, 1990;Müller et al, 2014;Peni, 2014;Kaur, Singh, 2018] ROA рассматривается как определяющий фактор в измерении успешности и эффективности компании. В [Peni, 2014] также дополнительно описывается Q Тобина как отображение переоцененности или недооцененности компании.…”
Section: методы оценки эффективности компанииunclassified